Analysis of the Natural Characteristics of the Plate Type Structure with Bolt Connection - DAI Ri-hui; LIU Lin-hui; MA Hui; XU Zhi-qiang; ZHAO Song-tao (Journal of Harbin University of Science and Technology, 2022)
In this paper, the finite element (FE) model of the plate-type structure with bolt connection is established based on ANSYS finite element analysis software. The prestressed modal method (PMM) is used to analyze the inherent characteristics of the system, and the accuracy of the obtained inherent frequencies is verified by comparing with the experimental results of the literature modal and the free vibration response of the system under impact excitation. Then, the effects of plate thickness, bolt size, and lap length of connection plate on the natural characteristics of the system under different preload forces were analyzed. Finally, the relationship between the system natural properties by the region bonding method (RBM) and the PMM is investigated. The results show that both plate thickness and bolt size have a large effect on the bending and torsion frequencies of the system, and the natural frequency of the system increases when the lap length of the connection increases. In the case of large preload force, the contact radius can be obtained by static contact analysis, and the corresponding nodes in the contact radius area are treated by the RBM with common nodes, and the calculated natural frequency of the system agrees well with the results obtained by the PMM.